2011
DOI: 10.1038/jcbfm.2011.125
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oxygen Metabolism of Rats using Injectable 15O-Oxygen with a Steady-State Method

Abstract: To develop a less-stressful and simple method for measurement of the cerebral metabolic rate of oxygen (CMRO 2 ) in small animals, the steady-state method was applied to injectable 15 O 2 -PET ( 15 O 2 -positron emission tomography) using hemoglobin-containing vesicles ( 15 O 2 -HbV). Ten normal rats and 10 with middle cerebral arterial occlusion (MCAO) were studied using a small animal PET scanner. A series of 15 O-PET scans with C 15 O-labeled HbV, H 2 15 O, and 15 O 2 -HbV were performed with 10 to 15 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Although precise evaluation of this estimation approach is needed because this is the first study to use the heart VOI in a 15 O-PET assay of oxygen metabolism by mice, the parameters in this study were obtained using ordinary equations that are widely applied both in clinical and basic settings and are similar to those reported in previous studies using rats (Supplementary Table). [8][9][10][11][12][13] Therefore, the OEF value obtained in this study appears to be adequate for mice. The recovery coefficient for the input function, which was obtained from the radioactivity concentration time course in the left ventricular cavity, was assumed to be 1.0 for calculations of CBF, CBV, OEF, and CMRO 2 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although precise evaluation of this estimation approach is needed because this is the first study to use the heart VOI in a 15 O-PET assay of oxygen metabolism by mice, the parameters in this study were obtained using ordinary equations that are widely applied both in clinical and basic settings and are similar to those reported in previous studies using rats (Supplementary Table). [8][9][10][11][12][13] Therefore, the OEF value obtained in this study appears to be adequate for mice. The recovery coefficient for the input function, which was obtained from the radioactivity concentration time course in the left ventricular cavity, was assumed to be 1.0 for calculations of CBF, CBV, OEF, and CMRO 2 .…”
Section: Discussionmentioning
confidence: 90%
“…where Hb and %Sat were hemoglobin concentration and O 2 saturation, which were fixed at 18.5 g/dl 9 and 96.7%, 12 respectively. Since several constants were assumed for the calculations as mentioned above, we simulated the effects of variations in the recovery coefficient on experimental parameters and present the results in a Supplementary document.…”
Section: Discussionmentioning
confidence: 99%
“…Reported values of OEF in rats under pentobarbital anesthesia are 54% 6 11% using the kinetic method with injectable 15 O-O 2 and 57% 6 13% using the surgical method based on the arterial-venous difference in oxygen concentration (4,20). Other studies using 15 O-O 2 hemoglobin-containing liposome vesicles reported OEF values in rats under chloral hydrate anesthesia of 61% 6 16% (6) and 56% 6 4% (27). OEF is a function of the 15 15 O-CO 2 count in the brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Injectable systems of 15 O 2 -carrier are expected to solve such problems. Injection of 15 O 2 -HbV has been proven to be effective for CMRO 2 to detect rat brain infarction [39,40]. …”
Section: Potential Usage Of Hbv As An Oxygen Carrier For Ischemic mentioning
confidence: 99%